2022
DOI: 10.3389/fpsyg.2022.856185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Risk for Orthorexia in Athletes Using the ORTO-15 Questionnaire: A Systematic Mini-Review

Abstract: The article aims to summarize the literature about the profile of risk of orthorexia in athletes using the ORTO-15 questionnaire. The search was performed at PubMed, Embase, Web of Science, and Sport Discus databases, using the terms “orthorexia” AND “athletes” with the respective entry terms. A multistage process of selection followed the PRISMA 2020 recommendation. A total of 688 articles were identified, and six studies were available for the final process. The prevalence of risk for orthorexia was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The pathological behavior of people affected by orthorexia focuses on the aspect of nutrition, including the detailed analysis of the composition of products consumed and the gradual elimination of those which may raise an affected person's doubts about their potentially negative impact on health. Planning the type, composition and handling of meals becomes the overriding goal each day, and the rejection of more and more products from the menu on the grounds that they are harmful can lead to serious health consequences, including malnutrition and secondary diseases resulting from nutritional deficiencies [7,10,19,20,21,22,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathological behavior of people affected by orthorexia focuses on the aspect of nutrition, including the detailed analysis of the composition of products consumed and the gradual elimination of those which may raise an affected person's doubts about their potentially negative impact on health. Planning the type, composition and handling of meals becomes the overriding goal each day, and the rejection of more and more products from the menu on the grounds that they are harmful can lead to serious health consequences, including malnutrition and secondary diseases resulting from nutritional deficiencies [7,10,19,20,21,22,28].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that are related to the development of this disorder are also discussed, and those particularly often described include: age, gender, BMI, educational profile (especially medical professions including dietitians) [1,2,7,10,13,16,18,20,21,25,27,28,29,20,21,22,23,27,28,29,30], and recent reports particularly emphasize the potential importance of chronic diseases and complaints requiring diet therapy, while also pointing out the paucity of data in this aspect [11,17,26]. Research findings on potential risk factors are highly divergent and one reason for this problem is attributed to the inadequacies of the ORTO-15 test [3,7,9,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ON is a recent eating behavior, and less is known about the prevalence in youth athletes. It was recently reported that higher values of ON can be presented in athletes as well as non-athletes 6 . The present study is the first up to now to describe the values of ON in youth female soccer players.…”
Section: Discussionmentioning
confidence: 93%
“…Orthorexia nervosa can be interpreted as a pathological fixation on healthy nutrition. The concept was introduced in the 90s but yet not recognized as an eating disorder by some organizations 6 .…”
Section: Introductionmentioning
confidence: 99%